(untitled) (Bangladesh Journal of Psychiatry, 2018)
Suffering from psychiatric illness is relatively common in epilepsy. There is now general agreement that incidence of neuro-behavioral disorders is higher in patients with epilepsy. The objective of the study was to find out the proportion of psychiatric disorders among the children suffering from epilepsy. It was a cross sectional study conducted during the period from July 2009 to June 2011 at the department of Paediatrics in Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh. In the study 104 children, aged 5-16 years, having epilepsy were purposively included and patients with febrile seizure were excluded. Data were collected through face-to-face interview using a semistructured questionnaire and diagnosis of psychiatric disorders was assigned according to the Diagnostic and Statistical Manual of Mental Disorders, 4th edition, text-revision (DSM-IV-TR). The results showed that among all patients 56.7% were male and 43.3% were female. Most of them (80.8%) were within 5-10 years of age. Among them, 57.7% of the cases had associated psychiatric disorders, where 21.2% had intellectual disability, 10.6% communication disorder, 7.7% learning disorder, 6.7% major depressive disorder, 5.8% ADHD and 1.9% had autistic disorder. This study suggests that significant number of children with epilepsy has been suffering from psychiatric illnesses. So, during diagnosis of epilepsy, early psychological assessment should be done. Bang J Psychiatry June 2016; 30(1): 7-9